Families, schools, and communities : together for young children - Couchenour, Donna (United States of America: Wadsworth, 2014)
This book emphasizes the role of families and communities in children's education, and is geared to meeting national standards in teacher preparation programs. Content reflects current research and best practices in education. Divided into two sections, this book helps you understand contemporary families and provides you with the skills that you will need to build relationships with families and the community. You'll find specific ideas and strategies for increasing family involvement in the community and schools, encouraging learning at home, working with military families, recognizing family strengths, diversity in the classroom, and many other topics. New content includes integration of current standards and a new video feature as well as expanded material on advocacy, technology, and strategies for dealing with parents.
Part I. Understanding families -- Part II. Practice .
Includes index.
Keywords: COMMUNITY AND SCHOOL; HOME AND SCHOOL